Social mediatization of Philippine politics determining the voting preference of first-time voters of Pantukan, Davao de Oro in the 2022 national elections - Pacres, Rona Dea A. (2023)
Social media, particularly Facebook, has become an extension of the public sphere where political campaigns happen, and has reshaped structures of contemporary political communication by influencing the way politicians and citizens interact with each other. The present scholarly research places a strong emphasis on exploring how first-time voters consume information and how it affects their voting preference during the presidential elections. This study analyzed how voting preferences of first-time voters were affected by political campaigns on Facebook. The study involved 120 registered first-time voters in Pantukan, Davao de Oro who became respondents of the survey which measured their exposure to political campaigns on Facebook and other sources of information and assessment of qualities, party competence and trustworthiness on presidential candidates. Findings revealed that exposure to Facebook has a positive significant relationship with leadership experience as a presidential quality. Aside from that, out of all the qualities, it also revealed that exposure to other sources of information, popularity, leadership experience, competence, knowledge on issues, and with campaign funds sufficiency has a high significant correlation. For assessment of party competence, it has a positive significant correlation with the first-time voters? exposure to Facebook and other sources of information. Chi-square tests and categorical regression were also run to examine the relationship and strength of variables and have shown some significant relationship to the voting preferences of first-time voters as they assess presidential candidates? qualities. There are also results of negative correlation which imply that there is a need for a reevaluation of voters? political behavior and an assessment of political dynamics in the country.